2013 IEEE 21st International Symposium on Modelling, Analysis and Simulation of Computer and Telecommunication Systems 2013
DOI: 10.1109/mascots.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Energy Consumption of Lossless Compression/Decompression Utilities on Mobile Computing Platforms

Abstract: Abstract-Data compression and decompression utilities can be critical in increasing communication throughput, reducing communication latencies, achieving energy-efficient communication, and making effective use of available storage. This paper experimentally evaluates several such utilities for multiple compression levels on systems that represent current mobile platforms. We characterize each utility in terms of its compression ratio, compression and decompression throughput, and energy efficiency. We conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The importance of lossless compression on consumer devices has been widely recognized [9]. This article complements our earlier study on Linux-based mobile development platforms with limited connectivity [10], [11] and other studies that were conducted about a decade ago [12], [13]. In contrast to these prior studies, here we consider the most recent compression utilities including some with parallel implementations, our setup supports more accurate energy measurements, and we use a state-of-the-art smartphone with four processor cores and wireless and cellular communication interfaces.…”
Section: Introductionmentioning
confidence: 56%
“…The importance of lossless compression on consumer devices has been widely recognized [9]. This article complements our earlier study on Linux-based mobile development platforms with limited connectivity [10], [11] and other studies that were conducted about a decade ago [12], [13]. In contrast to these prior studies, here we consider the most recent compression utilities including some with parallel implementations, our setup supports more accurate energy measurements, and we use a state-of-the-art smartphone with four processor cores and wireless and cellular communication interfaces.…”
Section: Introductionmentioning
confidence: 56%
“…A useful metric for describing efficiency of networked data transfers is the effective throughput, Th, expressed in megabytes per second [8]. For uncompressed file uploads Th.UUP is determined as US/T.UUP; for compressed file uploads the effective upload throughput is Th.CUP = US/(T.UUP/CR + T.C), where CR is the compression ratio.…”
Section: Methodsmentioning
confidence: 99%
“…The effective upload and download throughputs and energy efficiencies depend on many factors, including the file size and type, selected compression utility, the compression level, network characteristics such as latency and throughput, as well as the smartphone's performance and energyefficiency. Whereas previous studies showed that compressed uploads and downloads can save time and energy in many typical file transfers initiated from smartphones Dzhagaryan and Milenkovic, 2015;Milenkovic et al, 2013b) there is not a single upload or download file transfer method that works the best for all data types and network conditions. To underscore this problem, we conduct a measurement-based study that evaluates the effectiveness of various data transfer options under different network conditions.…”
Section: File Transfers In Mobile Cloudmentioning
confidence: 96%
“…The importance of lossless compression in network data transfers has also been recognized in academia (Barr and Asanović, 2003;2006;Dzhagaryan et al, 2013). Recent studies Milenkovic et al, 2013b) focused on a measurement-based experimental evaluation of compressed and uncompressed file transfers on the state-of-the-art mobile devices.…”
Section: Introductionmentioning
confidence: 99%